2019
DOI: 10.1002/aqc.3024
|View full text |Cite
|
Sign up to set email alerts
|

The Global Ocean Biodiversity Initiative: Promoting scientific support for global ocean governance

Abstract: Addressing the challenge of protecting biodiversity in the global ocean requires a sound knowledge and understanding of the complex marine environment. Since 2008 the Global Ocean Biodiversity Initiative (GOBI) has been established as a voluntary dedicated group of marine institutions and scientists working to support conservation and protection of marine biodiversity. A focus has been work to support the Convention on Biological Diversity's Ecologically or Biologically Significant Marine Area (EBSA) process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Alternatively, certain species may be considered as "leading" sentinels, whereby population level responses in these species precede observable change in responses of other species or the ecosystem (Hazen et al, 2019). The penguin species that breed in Antarctica and forage in the Southern Ocean, feed extensively on krill or are ice-obligates, and are exemplar species for studying the potential links between system fluctuations and predator populations (e.g., fisheries pressures: Hinke et al, 2017;Trathan et al, 2018;Watters et al, 2020), or Antarctic marine ecosystem responses to environmental perturbations (e.g., climate change: Jenouvrier et al, 2014;Johnson et al, 2019;Emmerson et al, 2015;. Indeed, evidence already shows that penguin populations in particular are at risk from overexploitation of resources and climate change (Boersma et al, 2019;Dias et al, 2019;Ropert-Coudert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, certain species may be considered as "leading" sentinels, whereby population level responses in these species precede observable change in responses of other species or the ecosystem (Hazen et al, 2019). The penguin species that breed in Antarctica and forage in the Southern Ocean, feed extensively on krill or are ice-obligates, and are exemplar species for studying the potential links between system fluctuations and predator populations (e.g., fisheries pressures: Hinke et al, 2017;Trathan et al, 2018;Watters et al, 2020), or Antarctic marine ecosystem responses to environmental perturbations (e.g., climate change: Jenouvrier et al, 2014;Johnson et al, 2019;Emmerson et al, 2015;. Indeed, evidence already shows that penguin populations in particular are at risk from overexploitation of resources and climate change (Boersma et al, 2019;Dias et al, 2019;Ropert-Coudert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The protection of these areas can also support sustained provision of ecosystem services. Furthermore, recent evidence has shown that in MPAs where fisheries operate and where the spatiotemporal distribution of marine IBAs are effectively accounted for in their design and management plans, these MPAs can provide effective conservation opportunities for seabird species and other marine top predators through appropriately designed spatiotemporal closures of fisheries operations (Heerah et al, 2019;Johnson et al, 2019;Handley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSP pillar of the EU's IMP is regulated by European Directive 2014/89/EU [17], and makes MSP mandatory in planning policies of all coastal Member States [18]. The MSP Directive requires the EU Member States to develop a national maritime spatial plan by 31 March 2021 [19,20], with a minimum review period of 10 years, and establishes an MSP framework, aimed at i) promoting the sustainable growth of maritime economies; ii) the sustainable development of marine areas; iii) the sustainable use of marine resources. Moreover, the Directive states that the minimum requirements for maritime spatial plans must include land-sea interactions, an ecosystem-based approach, coherence between MSP and other processes such as integrated coastal management, the involvement of stakeholders, the use of the best available data, transboundary cooperation between Member States, and cooperation with third countries [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, advocates of giving strong decisionmaking powers to a future BBNJ Scientific and Technical Body call for a "politically highly influential" design (De Santo, 2018). Increasingly, there are calls to include other forms of knowledge into policy-making across all package elements, including traditional knowledge of Indigenous Peoples and Local Communities (Dunstan et al, 2016;Ridings, 2018;Voigt-Hanssen, 2018;Johnson et al, 2019a;Scott, 2019; and the perspectives of resource managers, interest groups (De Santo, 2018), civil society actors, and the private sector (Kraabel, in press). This part of the BBNJ literature points to existing instruments (see Tables 4, 5), including: the Aarhus convention, with its general principles and approaches of public participation, transparency, and information availability (De Santo, 2018); the FAO's 2009 International Guidelines for the Management of Deep-sea Fisheries in the High Seas criteria for VME identification based on the best available scientific knowledge and expert judgment (Johnson et al, 2018); the CAMLR Scientific Committee (De Santo, 2018); scientific advice for decision-making in OSPAR and the North-East Atlantic Fisheries Commission (NEAFC) by the International Council for the Exploration of the Sea (ICES) (De Santo, 2018); and the Permanent Commission for the South Pacific (CPPS) with its climate-related scientific research across the region (Durussel et al, 2017).…”
Section: Science-policy Interfaces For Ocean Protectionmentioning
confidence: 99%